Dynamics of Singlet Oxygen Molecule Trapped in Silica Glass, Studied by Luminescence Polarization Anisotropy and Density Functional Theory - Skuja, Linards; Smits, Krisjanis; Trukhin, Anatoly; Gahbauer, Florian; Ferber, Ruvin; Auzinsh, Marcis; Busaite, Laima; Razinkovas, Lukas; Mackoit-Sinkevičienė, Mažena; Alkauskas, Audrius (American Chemical Society, 2020)
The lowest excited electronic state of the O2 molecule, a1Δg, the "singlet oxygen", is of utmost importance for photochemistry and photobiology. For O2 trapped in silica glass, the lifetime of this state and the associated a1Δg → X3ςg - photoluminescence (PL) is the longest known for O2 in any condensed medium at room temperature. We studied the temperature dependence, decay kinetics, and polarization anisotropy of this PL with 1064 nm excitation to the a1Δg(v = 1) state as well as with excitation to higher energies. PL at this excitation shows nonzero polarization anisotropy at 295 K, which increases with cooling to 14 K. At variance, excitation to higher energies yields depolarized PL. Polarization data indicate weak electric dipole character of the emission of the spin- and parity-forbidden a1Δg → X3ςg - transition, enabled by O2-SiO2 cage interactions. Density functional theory calculations indicate that at low temperatures the rotation of O2 is partially or fully frozen even in large silica voids. As the temperature increases, PL is increasingly depolarized by libration movement of O2 molecules. Analysis of O2 optical absorption in optical fibers allows one to obtain the absorption cross sections of X → a and X → b transitions of O2 in SiO2 glass and to evaluate both radiative and nonradiative rates of a → X luminescence.
The support from M-ERANET project “MyND” is acknowledged. A.A., M.M-S., and L.R. were supported by the Research Council of Lithuania (Grant M-ERA.NET-1/2015). The authors thank A. Pasquarello for providing the structures of the amorphous SiO 2 matrix for our computational work and K. Kajihara (Tokyo Metropolitan University) for valuable advice in PL kinetics measurements.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics